2017
DOI: 10.22334/jbhost.v2i1.42
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tourism to Poverty in Tourism Destination: Pro Poor Tourism Management Approach

Abstract: This study aims to determine the typology of poverty, the causes of poverty and the impact of tourism  on  the poor, in the region Tulamben and Candidasa, Karangasem district. Research using purposive sampling method with a sample size 94 respondents. The data analysis using quantitative descriptive analysis. The research results are as follows. Typology of poverty of coastal communities, among others: age dominated 60 years and over, low education (graduated SD), the average income of 300,000 / month.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 5 publications
0
3
0
2
Order By: Relevance
“…Odermatt indicated that mountain environments are rapidly changing and are susceptible to accelerated soil erosion, landslides and rapid loss of habitat and genetic diversity [3]. Furthermore, mountains are generally associated with widespread poverty [13]. All these specificities related to mountain areas imply that sustainable development of mountains is imperative if these environments are to be preserved for future generations.…”
Section: Introductionmentioning
confidence: 99%
“…Odermatt indicated that mountain environments are rapidly changing and are susceptible to accelerated soil erosion, landslides and rapid loss of habitat and genetic diversity [3]. Furthermore, mountains are generally associated with widespread poverty [13]. All these specificities related to mountain areas imply that sustainable development of mountains is imperative if these environments are to be preserved for future generations.…”
Section: Introductionmentioning
confidence: 99%
“…Dari sudut pandang perekonomian nasional, sektor pariwisata di pandang sebagai penyangga sektor nonmigas, dengan prioritas kegiatan yang diarahkan menjadi sektor andalan dalam penerimaan devisa, mendorong pembangunan dan pendapatan daerah. Menurut Cohen dampak pariwisata terhadap kondisi sosial ekonomi masyarakat lokal dapat dikategorikan menjadi delapan kelompok besar, yaitu dampak terhadap penerimaan devisa, dampak terhadap pendapatan masyarakat, dampak terhadap kesempatan kerja, dampak terhadap harga-harga, dampak terhadap distribusi manfaat/keuntungan, dampak terhadap kepemilikan dan kontrol, dampak pada pembangunan pada umumnya, dampak terhadap pembangunan pemerintah (Hastuti & Ismayanti, 2018;Khrisnamurti, Utami, & Darmawan, 2017;Maharani, Hanif, & Parji, 2021;Pitana & Diarta, 2009;Priono, 2011;Suardana & Sudiarta, 2017) Selain sebagai sumber pendapatan devisa, pariwisata juga memberikan kontribusi untuk penciptaan lapangan kerja, kegiatan produksi dan pendapatan nasional (PDB), pertumbuhan sektor swasta dan pembangunan infrastruktur. Pariwisata juga berpotensi mendorong peningkatan penerimaan negara dari pajak, terutama pajak tidak langsung.…”
Section: Pendahuluanunclassified
“…Menurut Cohen pada tahun 1984, dampak pariwisata terhadap kehidupan sosial ekonomi masyarakat lokal dapat dikategorikan menjadi delapan kelompok, yaitu (1) penerimaan devisa; (2) pendapatan masyarakat; (3) kesempatan kerja; (4) hargaharga; (5) distribusi manfaat atau keuntungan; (6) kepemilikan dan kontrol; (7) pembangunan pada umumnya; (8) pembangunan pendapatan pemerintah (Hastuti & Ismayanti, 2018;Khrisnamurti et al, 2017;Maharani et al, 2021;Priono, 2011;Suardana & Sudiarta, 2017).…”
Section: Dampak Pariwisata Terhadap Ekonomi Masyarakatunclassified
“…The existence of coastal tourism will have a positive impact on the local community if they can participate in taking advantage of it as a new business opportunity. On the other hand, this condition will have a negative impact on their livelihoods and will only reduce the ecological quality of the coast if all economic actors are not able to maintain environmental sustainability (Lopes et al (2015); Wu and Tsai (2016); Suardana and Sudiarta (2017); Khrisnamurti et al (2017); Maliao et al (2017).…”
Section: Introdutionmentioning
confidence: 99%